딥러닝기반 감정인식에서 데이터 불균형이 미치는 영향 분석 - 노하진; Hajin Noh; 임유진; Yujin Lim (정보처리학회논문지. KIPS transactions on computer and communication systems 컴퓨터 및 통신 시스템, 2023)
최근 들어 영유아를 대상으로 한 비대면 상담이 증가함에 따라 감정인식 보조 도구로 CNN기반 딥러닝 모델을 많이 사용하고 있다. 하지만 대부분의 감정인식 모델은 성인 데이터 위주로 학습되어 있어 영유아 및 청소년을 대상으로 적용하기에는 성능상의 제약이 있다. 본 논문에서는 이러한 성능제약의 원인을 분석하기 위하여 XAI 기법 중 하나인 LIME 기법을 통해 성인 대비 영유아와 청소년의 감정인식을 위한 얼굴 표정의 특징을 분석한다. 뿐만 아니라 남녀 집단에도 동일한 실험을 수행함으로써 성별 간 얼굴 표정의 특징을 분석한다. 그 결과로 연령대별 실험 결과와 성별별 실험 결과를 CNN 모델의 사전 훈련 데이터셋의 데이터 분포를 바탕으로 설명하고 균형 있는 학습 데이터의 중요성을 강조한다. In recent years, as online counseling for infants and adolescents has increased, CNN-based deep learning models are widely used as assistance tools for emotion recognition. However, since most emotion recognition models are trained on mainly adult data, there are performance restrictions to apply the model to infants and adolescents. In this paper, in order to analyze the performance constraints, the characteristics of facial expressions for emotional recognition of infants and adolescents compared to adults are analyzed through LIME method, one of the XAI techniques. In addition, the experiments are performed on the male and female groups to analyze the characteristics of gender-specific facial expressions. As a result, we describe age-specific and gender-specific experimental results based on the data distribution of the pre-training dataset of CNN models and highlight the importance of balanced learning data.